Developing an International Pool of Certified Quality Reviewers. Issue 3 (3rd July 2017) - Adair, Deborah
ABSTRACT: This article covers the origins, growth, rationale, calibration, and inspiration of an international pool of certified Quality Matters TM (QM) Peer Reviewers. From the beginning in 2003, as a U.S. Department of Education, Fund for the Improvement of Postsecondary Education funded project, QM was developed as a faculty-centered, peer-based approach for quality assurance and continuous improvement in online education. Development of a pool of qualified peer reviewers grew out of the QM professional development sequence that faculty found transformative for their own course development and teaching practice. Rigorous processes for maintaining the integrity of QM Peer Reviewer certification are discussed. The case is made that QM Peer Review is scalable and affordable for academic institutions. Rather than limiting the execution of quality review to a particular unit or administrative role, engaging faculty in the review function allows for a greater number of reviewers to handle the review tasks at a lower cost to the institution. For peer review to remain "a gift, and not a burden" for faculty and to ensure fit for purpose, the QM Peer Review process will need to evolve to respond to new needs for quality assurance.